Race and Sex Differences in QRS Interval and Associated Outcome Among Patients with Left Ventricular Systolic Dysfunction. Issue 3 (March 2017) - Randolph, Tiffany C.; Broderick, Samuel; Shaw, Linda K.; Chiswell, Karen; Mentz, Robert J.; Kutyifa, Valentina; Velazquez, Eric J.; Gilliam, Francis R.; Thomas, Kevin L.
Abstract : Background: Prolonged QRS duration is associated with increased mortality among heart failure patients, but race or sex differences in QRS duration and associated effect on outcomes are unknown. Methods and Results: We investigated QRS duration and morphology among 2463 black and white patients with heart failure and left ventricular ejection fraction ≤35% who underwent coronary angiography and 12‐lead electrocardiography at Duke University Hospital from 1995 through 2011. We used multivariable Cox regression models to assess the relationship between QRS duration and all‐cause mortality and investigate race‐QRS and sex‐QRS duration interaction. Median QRS duration was 105 ms (interquartile range [IQR], 92–132) with variation by race and sex ( P <0.001). QRS duration was longest in white men (111 ms; IQR, 98–139) followed by white women (108 ms; IQR, 92–140), black men (100 ms; IQR, 91–120), and black women (94 ms; IQR, 86–118). Left bundle branch block was more common in women than men (24% vs 14%) and in white (21%) versus black individuals (12%). In black patients, there was a 16% increase in risk of mortality for every 10 ms increase in QRS duration up to 112 ms (hazard ratio, 1.16; 95% CI, 1.07, 1.25) that was not present among white patients (interaction, P =0.06). Conclusions: Black individuals with heart failure had a shorter QRS duration and more often had non‐left bundle branch block morphology than white patients. Women had left bundle branch block more commonly than men. Among black patients, modest QRS prolongation was associated with increased mortality.